2015
DOI: 10.1097/gox.0000000000000417
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Changes of Maxilla after Secondary Alveolar Cleft Repair

Abstract: Background:Recombinant human bone morphogenetic protein (rhBMP)-2 has been used as an alternative to autologous bone transferring, a standard method of treatment. However, its potential adverse effect on anterior maxillary arch is unknown. Thus, the purpose of this study was to quantify sagittal and transversal changes of anterior maxilla after secondary alveolar cleft repair using traditional iliac crest bone grafting versus rhBMP-2.Methods:Twelve unilateral complete cleft lip and palate patients were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The clinical data on the effect of rhBMP-2 on craniofacial growth are very limited. Studies by Alonso et al 54 and Raposo-Amaral et al 57,59 found no significant difference in nasal symmetry at 6 postoperative months, and no significant changes in upper lip and nostril anatomy or maxillary cephalometric proportions on three-dimensional CT at 1 year. Longer-term follow-up is lacking, and the studies had small sample sizes unequally randomized into rhBMP-2 and ICBG groups, with an even smaller number of patients undergoing imaging.…”
Section: Discussionmentioning
confidence: 87%
“…The clinical data on the effect of rhBMP-2 on craniofacial growth are very limited. Studies by Alonso et al 54 and Raposo-Amaral et al 57,59 found no significant difference in nasal symmetry at 6 postoperative months, and no significant changes in upper lip and nostril anatomy or maxillary cephalometric proportions on three-dimensional CT at 1 year. Longer-term follow-up is lacking, and the studies had small sample sizes unequally randomized into rhBMP-2 and ICBG groups, with an even smaller number of patients undergoing imaging.…”
Section: Discussionmentioning
confidence: 87%